Hukum Perempuan Sholat Berjamaah di Masjid - Cholidi Cholidi; Zuraidah Zuraidah (Muqaranah, 2023)
Congregational prayers in Islam have added value. Likewise praying in the mosque has additional appreciation from Allah Subhanahu wa Ta'ala. Especially if the prayers are performed in congregation and carried out in the mosque. But in daily reality there are those who judge that congregational prayers performed at the mosque by women are not a good deed. Therefore, this article discusses the issue of how the law holds congregational prayers for women in mosques according to the perspective of madhhab scholars. The purpose of this study was to examine the legal basis for congregational prayers at the mosque for women based on the opinion of the Islamic scholars. This research is a literature research by examining the treasures of the book referred to by the school's scholars. From searching this article, it was found that the opinion of madhhab scholars absolutely prohibits (forbids) women from participating in congregational prayers at the mosque.